i-Dashboard: real-time business intelligence for decision support - Siraj, Fadzilah; Abu Bakar, Nur Azzah; Yusoff, Nooraini; Ahmad, Abdul Razaq; Sahazudin, Faizzudin (2015)
RAKANNUSA CORPORATION (M) SDN BHD has been in operation since the year 2000.It is a PETRONAS registered manufacturer and supplier for the petroleum industry in Malaysia. As the company aims to open up as many new business opportunities as possible through mutually beneficial collaborations with esteemed customers and strategic partners worldwide, it is very important that the management is able to monitor, plan, communicate and evaluate its financial and resources in a timely manner.A monitoring tool known as I-Dashboard is to transfer to RAKANNUSA in order to facilitate faster decision making by the management.Initially, RAKANNUSA requirement has been gathered based on the three major types of businesses, namely, Services, Trading and Manufacturing.This paper presented I-Dashboard for RAKANNUSA that provides a multiple - screen display of its related department that supports in decision making.In addition, the Finance Department provides the financial status of the company whereas the Technical and Sales Department provides the sales track record, current status of inventory and product movement. The Human Resource Department indicates the manpower available to carry out the request from the clients. The dynamic graphs are generated by integrating the information by the above mentioned departments.Hence, I-Dashboard is used as the main platform to integrate data from various departments, process the information and to communicate between departments so that, the top management is able to make quick decisions. The tailored I-Dashboard information shows that this project has successfully achieved its target in transferring the knowledge between university academia and industry.